2013
DOI: 10.3109/07434618.2013.818059
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Efficacy of the Picture Exchange Communication System (PECS) versus a Speech-Generating Device: Effects on Social-communicative Skills and Speech Development

Abstract: The Picture Exchange Communication System (PECS) and a speech-generating device (SGD) were compared in a study with a multiple baseline, alternating treatment design. The effectiveness of these methods in increasing social-communicative behavior and natural speech production were assessed with three elementary school-aged children with severe autism who demonstrated extremely limited functional communication skills. Results for social-communicative behavior were mixed for all participants in both treatment con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 45 publications
2
26
0
1
Order By: Relevance
“…Sometimes, the treatment package that involves speech output is compared to a control condition involving no aac modalities (e.g., Kasari, Kaiser, Goods, nietfield, & Mathy, 2014). Second, two aac treatment packages may be compared to one another, whereby one package includes a speech output technology and the other package includes aac modalities other than speech output (e.g., Boesch, Wendt, Subramanian, & hsu, 2013a). Third, speech output may be isolated as an independent variable to study its specific impact when comparing the presence versus absence of speech output; for example, Parsons and laSorte (1993) studied whether the use of a computer-based SGd with the speech output on would result in greater vocalizations in children with autism than with the speech output off.…”
Section: How the Effects Of Speech Output Have Been Studiedmentioning
confidence: 99%
“…Sometimes, the treatment package that involves speech output is compared to a control condition involving no aac modalities (e.g., Kasari, Kaiser, Goods, nietfield, & Mathy, 2014). Second, two aac treatment packages may be compared to one another, whereby one package includes a speech output technology and the other package includes aac modalities other than speech output (e.g., Boesch, Wendt, Subramanian, & hsu, 2013a). Third, speech output may be isolated as an independent variable to study its specific impact when comparing the presence versus absence of speech output; for example, Parsons and laSorte (1993) studied whether the use of a computer-based SGd with the speech output on would result in greater vocalizations in children with autism than with the speech output off.…”
Section: How the Effects Of Speech Output Have Been Studiedmentioning
confidence: 99%
“…A limited number of studies involving individuals with ASD or related developmental disabilities have evaluated the effects of speech‐generating devices (SGD) on vocalizations (e.g., Beck, Stoner, Bock, & Parton, ; Boesch, ; Kasari et al, ; Parsons & La Sorte, ; Roche et al, ; Schlosser et al, ; Sigafoos et al, , ). It has been suggested that in comparison to AAC systems without speech output, SGDs might provide particular advantages for increasing vocal speech (Blischak et al, ; Kasari et al, ; Schlosser & Wendt, ).…”
mentioning
confidence: 99%
“…Finally, Boesch et al . () showed that social–communicative behaviours occurred more frequently in phase II and less frequently in phases I and III of the PECS training. The authors speculated that opportunities to make eye contact with the communicative partner increased during phase II with respect to phases I and III because in phase II participants had to scan the room to locate the communicative partner prior to engaging in the communicative exchange.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, Boesch et al . () compared PECS training and a speech‐generating device (SGD) in a multiple baseline, alternating treatment design on three children with severe autism. Results showed that although relatively little difference was observed between PECS and SGD treatments, PECS training (in particular phase II) proved to be helpful in encouraging social–communicative skills.…”
Section: Discussionmentioning
confidence: 99%